HCV Ab titer and ALT level indicate occult hepatitis C virus infection in treatment-naive HCV Ab-positive and HCV Ab-negative patients: a 3-year prospective cohort study - Ming-Ling Chang; Wei-Ting Chen; Li-Heng Pao; Cheng-Hsun Chiu; Rong-Nan Chien (Microbiology Spectrum)
ABSTRACT The phenotype of occult hepatitis C virus (HCV) infection (OCI) in anti-HCV treatment-naive patients remains elusive. A prospective 3-year cohort study of 218 anti-HCV treatment-naive patients was conducted. OCI was defined as positive HCV RNA in peripheral blood mononuclear cells (PBMCs) of patients with negative serum HCV RNA. Among the 128 HCV antibody (Ab)-positive patients, 15 (11.7%) had OCI; higher HCV Ab titers were noted in patients with OCI than in those without OCI (84.25 ± 64.76 vs 46.60 ± 46.07 ng/mL, P = 0.006), and the HCV Ab titer was a marker of OCI (cutoff: >53.2 ng/mL). The 3-year cumulative incidence (CI) of cardiovascular events was greater in patients with OCI than in those without OCI (84% vs 46.4%, P = 0.043). Among the 90 HCV Ab-negative patients, 5 (5.6%) had OCI; the alanine aminotransferase (ALT) levels were greater in patients with OCI than in those without OCI (114.4 ± 71.6 vs 67.2 ± 87.4 U/L, P = 0.035). A greater CI of autoimmune disease was noted in patients with OCI than in those without OCI (20% vs 1.2%, P = 0.006). Among anti-HCV treatment-naive patients, the prevalence rates of OCI were 11.7% in HCV Ab-positive patients and 5.6% in HCV Ab-negative patients. High HCV Ab titers in HCV Ab-positive patients require caution regarding OCI and cardiovascular events, and cryptogenic hepatitis warrants suspicion of OCI and autoimmune diseases.IMPORTANCEAmong anti-HCV treatment-naive patients, the prevalence rates of OCI were 11.7% in HCV Ab-positive patients and 5.6% in HCV Ab-negative patients. High HCV Ab titers (cutoff: >53.2 ng/mL) in HCV Ab-positive patients require caution regarding OCI and cardiovascular events, and cryptogenic hepatitis warrants suspicion of OCI and autoimmune diseases.